Ocena stosowania marketingu relacji przez polskie biura podróży w świetle badań ankietowych - Dudek, Andrzej; Michalska-Dudek, Izabela (Assessment of Using Relationship Marketing by Polish Travel Agencies in the Light of Questionnaire Survey, 2007)
The paper presents the essence of the relationship marketing concept. There are also described results of the questionnaire survey, which estimated the level of application of marketing relationship in practice on travel agencies in Poland. Factors determining the use of relationship marketing in investigated population have been distracted using classification trees. The results of analysis show that the size of travel agencies measured in number of employees and type of business activity are main determinants.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 101-109